People, livelihoods and Multiple-Use Water Services (MUS) - van Koppen, Barbara (CGIAR Challenge Program on Water and Food, 2009)
The CPWF’s MUS team includes researchers and implementers from the domestic and productive water sub-sectors. Partners are the International Water Management Institute, the International Water and Sanitation Centre, International Development Enterprises, and 18 national and regional farmer networks, NGOs, government agencies, and universities in eight countries in five river basins: the Andes System (Bolivia and Colombia), Indus-Ganges (India and Nepal), Limpopo (South Africa and Zimbabwe), Mekong (Thailand), and Nile basins (Ethiopia). Winrock International led an economic analysis of CP-MUS cases and other case studies. CPWF MUS piloted the MUS approach in 25 study areas.